Population Genomic Analysis Reveals Contrasting Demographic Changes of Two Closely Related Dolphin Species in the Last Glacial. (28th May 2018) - Vijay, Nagarjun; Park, Chungoo; Oh, Jooseong; Jin, Soyeong; Kern, Elizabeth; Kim, Hyun Woo; Zhang, Jianzhi; Park, Joong-Ki
Abstract: Population genomic data can be used to infer historical effective population sizes ( N e ), which help study the impact of past climate changes on biodiversity. Previous genome sequencing of one individual of the common bottlenose dolphin Tursiops truncatus revealed an unusual, sharp rise in N e during the last glacial, raising questions about the reliability, generality, underlying cause, and biological implication of this finding. Here we first verify this result by additional sampling of T. truncatus . We then sequence and analyze the genomes of its close relative, the Indo-Pacific bottlenose dolphin T. aduncus . The two species exhibit contrasting demographic changes in the last glacial, likely through actual changes in population size and/or alterations in the level of gene flow among populations. Our findings suggest that even closely related species can have drastically different responses to climatic changes, making predicting the fate of individual species in the ongoing global warming a serious challenge.